Analisis Diplomasi Soft Power Denmark Terhadap Indonesia (Studi Tentang Kerja Sama Pengelolaan Lingkungan di Indonesia) [An Analysis of Denmark’s Soft Power Diplomacy in Indonesia (A Study nn Environmental Management Coorperation in Indonesia)] - Septyanto Galan Prakoso; Nadia Dian Ardita; Andriansyah Perdana Murtyantoro (Sekretariat Jenderal DPR RI, 2019)
Global warming is one of the key issues of the century. The cause of this particular phenomenon is that most economic activities have been carried out by many countries without due consideration of sustainability and the environment. Due to the lack of awareness of both aspects, the Earth’s temperature is getting warmer over the past few years and the long-term effect of such trend is that the sea level has started to rise. Coastal countries start to witness its impacts and some of them have already taken several actions to address this problem. Among the few countries that are determined to take serious measures to address this issue is Denmark. Through its Ministry of Foreign Affairs, Denmark has worked in cooperation/collaboration with countries that have contributed to this environmental problem in slowing down the phase of global warming by looking directly at its source. In response to this situation, back in November 2017, Denmark’s Prime Minister Lars Løkke Rasmussen visited Jakarta to discuss issues of Denmark’s interest in Indonesia, especially about environmental issue in Indonesia. The meeting was marked by a commitment of strengthened relations between two countries, and an exchange of gifts between both leaders. This study aims to find out the reasons why Denmark wanted to cooperate with Indonesia in surmounting environmental problems, and what actions the Danish government has taken to decrease the rate of pollution in Indonesia through the adoption of the National Interest concept. Towards the end, this article shows that Denmark has built several green facilities in order to decrease the pollution level, which partially comes from Indonesia. AbstrakPemanasan global merupakan isu yang penting pada abad ini. Sumber dari terjadinya fenomena ini adalah aktivitas ekonomi yang dilakukan oleh Negara-negara di dunia tidak memperhatikan aspek lingkungan hidup dan keberlanjutan. Sebagai akibat dari kurangnya aspek-aspek tersebut menyebabkan meningkatnya temperatur bumi dalam beberapa tahun terakhir. Hal ini kemudian menyebabkan dampak jangka panjang yaitu naiknya permukaan air laut. Negara-negara pesisir mulai merasakan dampak dan melakukan berbagai usaha untuk menghadapi isu lingkungan ini. Denmark menjadi salah satu negara yang berkeinginan untuk mengatasi masalah ini. Melalui Kementerian Luar Negerinya, Denmark telah melakukan kerja sama dengan negara-negara yang menjadi kontributor penyebab masalah lingkungan ini dengan tujuan untuk memperlambat laju pemanasan global. Melihat situasi ini, Perdana Menteri Denmark, Lars Løkke Rasmussen, melakukan kunjungan ke Indonesia pada November 2017. Kunjungan kenegaraan ini bertujuan untuk membahas kepentingan nasional Denmark terhadap Indonesia, khususnya mengenai isu lingkungan hidup. Pertemuan ini ditandai dengan pemberian hadiah diplomatik antara kedua negara. Tulisan ini bertujuan untuk mengetahui mengapa Denmark ingin bekerja sama dengan Indonesia dalam mengatasi isu lingkungan serta tindakan apa yang pemerintah Denmark lakukan dalam mengurangi tingkat polusi di Indonesia dengan menggunakan konsep National Interest. Bagian terakhir jurnal ini menunjukkan hasil konkrit kerjasama Indonesia-Denmark yaitu dibangunnya fasilitas-fasilitas yang berorientasi Hijau untuk mengurangi polusi yang sebagian dihasilkan oleh Indonesia.